(untitled) (Research, Society and Development, 2020)
The pandemic caused by the new coronavirus has acquired great proportions and its impact on society has become increasingly significant. With regard to education, the remote learning is used as an alternative to keep the students active, minimizing the consequences that the policies of social isolation has been had on academic activities. This study, has a descriptive, qualitative and quantitative character, as an experience report, and was elaborated based on the need for sudden adaptation of the pedagogical strategies in the course of Histology and Embryology of the Dentistry School of a Brazilian public university. The objective is to expose the different possibilities of strategies and pedagogical tools that have been used, as well as to analyze the academic performance and engagement of students. Teachers sought tried not only temporary solutions to continue the course, but strive to recreate a new educational model, considering the use of active teaching methodologies for meaningful learning, through the use of pedagogical strategies and fully used digital tools in a virtual way, providing opportunities for the development of students’ autonomy and self-responsibility. Although preliminary results regarding student engagement and performance has been promising, this study is limited to data at a defined time and there would be a need for longitudinal studies to effectively assess the impacts of this educational model, not just on student engagement and performance, but also in their learning and the quality of education.